Rol del antropólogo forense en las pericias somatológicas y facial en la Unidad Médico Legal II Loreto 2025 - Pupuche Pacaya, Betsy Mariel (2025)
The thesis “Role of the forensic anthropologist in somatological and facial expertise in the Legal Medical Unit II Loreto 2025” analyzes how the forensic anthropologist works within the legal system of Loreto, specifically in somatological and facial expertise. 24 expert reports carried out between 2022 and 2025 were reviewed, focused on cases of aggravated robbery. The study shows that, although standardized methods are applied (such as morphological-comparative analysis and the use of software such as Amped FIVE), the results are affected by low image quality, inadequate angles and facial coverage. The results: 21 reports with partial coincidence, 2 with full identification and 1 inconclusive. It is highlighted that the work of the anthropologist is not only technical, but directly influences judicial decisions, especially in regions like Loreto, where there is often no other type of evidence. The thesis also includes methodological, ethical reflections and personal experiences of the investigator, which show the real challenges of forensic work in a region with few resources. The main contribution: make visible a key but little-recognized work within the criminal process, and demonstrate that, with few means, forensic experts in Loreto manage to technically support decisions that affect the freedom or conviction of a person